Unlocking Gen Z Creativity: Soft Skill Kunci Menghadapi Dinamika Karier Masa Depan - Diana Zumrotus Sa’adah; Septi Tri Dinanti; Mahrifatun Khasanah; Mona Chairun Nisa; Asih Tri Utami; Okta Febriansyah (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
The rapid development of technology and the dynamic global labor market require young generations, particularly Generation Z, to possess career readiness that is determined not only by technical skills but also by non-technical competencies, or soft skills. This study aims to analyze the role of soft skills, particularly creativity, in shaping the career preparedness and success of Generation Z. Literature synthesis indicates that Generation Z excels in digital literacy and technological adaptability but still faces challenges in social and emotional competencies, such as effective communication, empathy, and cross-generational collaboration. The imbalance between hard skills and soft skills affects work effectiveness, career mobility, and the ability to build professional networks. Creativity emerges as a strategic soft skill that enhances motivation, innovation, and productivity, and can be developed through the integration of soft and hard skills, project-based learning approaches, educational technology, and the strengthening of self-efficacy. The study also identifies challenges in fostering creativity in real workplace environments, including hierarchical organizational cultures and limited mechanisms for rewarding new ideas. Based on these findings, it is recommended that educational institutions, industries, and policymakers collaborate to create a sustainable ecosystem for soft skills development, enabling Generation Z to become innovative and adaptive change agents in a competitive global career landscape.